An analysis of the Class 1 Gene region in sheep major histocompatibility complex - Siva Subramaniam, Nitthiya (Curtin University, 2012)
The major histocompatibility complex (MHC) is a chromosomal region associated with immune responsiveness in vertebrates. Over four decades many studies have demonstrated important associations between MHC loci and disease resistance or susceptibility in a variety of mammals, especially humans and mice. However, characterisation of the sheep MHC has not been widely studied compared to other domestic species. Since sheep provide food and fibre to many of the world’s populations, and is a major industry in Australia a better understanding of the sheep MHC will deliver many benefits when used in conjunction with the new field of genomics, such as the marker assisted selective breeding.This will be of particular benefit for traits that are difficult to improve by conventional selection - especially those that have low heritability, or are expensive to breed for by phenotypic selection. The main aims of this study are to characterise better the genomic architecture of the sheep MHC class I region and to explore structure function relationships of some of the many loci therein. Essential to these aims is the discovery of polymorphic loci, especially SNPs, and the identification of haplotypic elements for association studies and patterns of recombination within this region.Bacterial artificial chromosomes (BACs) containing sub-regions of the sheep MHC class I region were sub-cloned and sequenced. Contiguous sequences were then re-assembled to generate a physical map of MHC class I region. Single nucleotide polymorphisms (SNPs) within the sheep MHC class I region were identified by polymerase chain reaction (PCR) amplification and sequencing of specific loci in a small population of unrelated sheep. Subsequently, a panel of SNPs spanning the class I region were chosen to genotype a population of distantly related 108 animals to develop a linkage disequilibrium (LD) map, and identify possible recombination hotspots relative to the LD blocks within this region. In addition, the SNP genotypes were used to predict haplotypes within the sheep MHC class I region.In conjunction with these studies, a small population of homozygous sheep was produced by sire-daughter mating for identification of discrete immune related genes within the class I region. This strategy was considered necessary to reduce allelic variation thereby facilitating the detection of discrete class I loci within a region noted for multiple copies of classical (Ia) and non-classical (Ib) class I genes, as well as probable pseudogenes. MHC class I gene sequences derived from homozygous sheep were supplemented with published reference sequences of different breeds. The many sheep sequences obtained were subjected to multiple sequence alignments and phylogenetic analysis in order to estimate the number of discrete loci present.The SNP panel generated in this project was also used for association studies with wool production traits in sheep and class I haplotypes. In particular, intragenic genotypes and haplotypes from the skin and hair related Corneodesmosin (CDSN) gene were analysed in 107 sheep with known estimated breeding values (EBV) for clean fleece weight (CFW), fibre diameter (FD) and staple strength (SS).The work described herein produced a comprehensive physical map of the sheep MHC class I region, which includes information relating to gene location and organisation. Immune related class I genes are clustered into 3 blocks; beta, kappa and a novel block not previously identified in other organisms. The organisation of other MHC class I genes is similar to that present in the cattle MHC except for a re-arrangement of a cluster of TRIM genes. Thirty two SNPs were identified from 14 distinct loci within the MHC class I region. Linkage analysis with a selected panel of 14 SNPs spanning approximately 505 kbp of the class I region revealed four blocks characterised by high linkage disequilibrium. Genotyping of 108 animals with this SNP panel permitted the prediction of thirty four unique haplotypes, which accounted for approximately 90% of haplotype frequency.Two of these haplotypes showed associations with wool production traits, suggesting that the SNPs analysed within MHC class I could be part of an extended haplotype influencing for wool traits. Classification of MHC classical (Ia) and non-classical genes into loci resulted in identification of 14 loci in the sequences analysed. A few of the loci identified show breed specific characteristics and explains possible evolutionary history of the loci in different breeds of sheep. Analysis of SNPs within CDSN showed that the gene, which is located in the MHC class I region has an association with fineness of wool in sheep. Five SNPs within the coding region showed reduced EBV for fibre diameter when present in a homozygous state.This project has resulted therefore in an improved physical map of the class I region in the sheep MHC, the identification and annotation of several new genes, together with genotypic and haplotypic associations with productivity traits in sheep that will be of immediate interest to the wool industry. As often is the case, the resulted obtained have generated more questions that relate to the structure, function and evolution of this fascinating genomic region that is a critical modulator of the adaptive immune response in vertebrates.